دليل الاختبا ا رت والمعايير - الطبعة المنقحة الثامنة - United Nations Economic Commission for Europe (United Nations, 2024)
The Manual of Tests and Criteria contains criteria, test methods and procedures to be used for the classification of dangerous goods according to the provisions of the “United Nations Recommendations on the Transport of Dangerous Goods, Model Regulations”, as well as of chemicals presenting physical hazards according to the “Globally Harmonized System of Classification and Labelling of Chemicals (GHS)”. It therefore also supplements national or international regulations which are derived from the Model Regulations or the GHS. Originally developed by the Economic and Social Council’s Committee of Experts on the Transport of Dangerous Goods, which adopted a first version in 1984, the Manual of Tests and Criteria has been regularly updated and amended. Currently, the updating is done under the auspices of the Committee of Experts on the Transport of Dangerous Goods and on the Globally Harmonized System of Classification and Labelling of Chemicals, which replaced the original committee in 2001.